Improvement of structural, thermal and mechanical properties of epoxy composites and bonded joints exposed to water environment by incorporating boron nanoparticles - Korkmaz, Yasemin; Gultekin, Kursat (ELSEVIER SCI LTD, 2022)
This research aims to investigate the effects of hexagonal boron nitride (h-BN) and hexagonal boron carbide (hB(4)C) nanoparticles on the epoxy composites and single lap joints against hydrothermal ageing and resultant degradations of mechanical, thermal and structural properties. The undoped, h-BN and h-B4C nanoparticles doped epoxy composites and single lap joints were fabricated and then exposed to distilled water for 20, 40, and 60 days. Water absorption, FT-IR, SEM, DSC, DMA and tensile tests were performed to characterize the epoxy composites after hydrothermal ageing. In addition, a tensile test was performed to determine the failure load of the single-lap joints bonded with undoped, h-BN and h-B4C doped epoxies. It was seen from the experimental results that the ageing time and the doping of boron nanoparticles into the epoxy resin changed the rates of degradation. The degradation in the mechanical and thermal properties of h-BN and h-B4C nanoparticles doped epoxy composites occurred to a lower extent than undoped epoxy. After 60 days of the hydrothermal ageing, the storage modulus and the tensile strength of undoped epoxy composites decreased by approximately 30% and 29%, while these degradation rates were determined as 16% and 18% in the h-BN doped epoxy composites, respectively. Similarly, the degradation of thermal and mechanical properties of h-B4C nanoparticle doped composites is lower than that of undoped composites. Additionally, it was observed that the joints bonded with hBN and h-B4C doped epoxies exhibited better mechanical performance after the hydrothermal ageing. The failure load of the undoped, h-BN and h-B4C & nbsp; doped epoxy joints was decreased by 34%, 19% and 20% at the end of 60 days of ageing, respectively. The results of this research work are thought to benefit the wide and safe application of epoxy resin systems in engineering applications.
Keywords: Hydrothermal ageing; Boron nanoparticles; Epoxy; Nanocomposites; Mechanical properties; DIELECTRIC-PROPERTIES; ABSORPTION; RESIN; DEGRADATION; ADHESIVES; BEHAVIOR; Engineering; Materials Science